2005
DOI: 10.1002/jcc.20265
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of hydrated NH: An ab initio QM/MM molecular dynamics simulation

Abstract: A combined ab initio quantum mechanical/molecular mechanical (QM/MM) molecular dynamics simulation has been performed to investigate solvation structure and dynamics of NH(4) (+) in water. The most interesting region, the sphere includes an ammonium ion and its first hydration shell, was treated at the Hartree-Fock level using DZV basis set, while the rest of the system was described by classical pair potentials. On the basis of detailed QM/MM simulation results, the solvation structure of NH(4) (+) is rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 56 publications
4
45
0
Order By: Relevance
“…For example, the Car–Parrinello dynamics has been applied to examine the hydration of Cl − , Li + , and Na + ions. Other examples are the QM/MM dynamics simulations of the Cl − , Li + , Na + , and NH4+ . Those theoretical investigations have contributed significantly to our understanding of those hydrated ions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Car–Parrinello dynamics has been applied to examine the hydration of Cl − , Li + , and Na + ions. Other examples are the QM/MM dynamics simulations of the Cl − , Li + , Na + , and NH4+ . Those theoretical investigations have contributed significantly to our understanding of those hydrated ions.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the B3LYP calculations, although they provide reasonable geometries, predict too strong ion-water interactions, most probably due to an overestimation of the correlation energy. 54,56 From the data shown in Table 1, the contributions of electron correlation to the binding energies were estimated to be about 5%. This can be expected to have a significant influence on structural and dynamical properties of hydrated H 3 O þ .…”
Section: Methodsmentioning
confidence: 99%
“…[44] that a complete understanding of the water exchange mechanisms requires information on both hydration structures and dynamics, which are closely related to the interactions and momentum transfer between water molecules in the first and second hydration shells. The influence of water molecules in the second hydration shell was also illustrated in our previous work on [NH 4 + ] aq [73] and [H 3 O + ] aq [74]. Especially in the case of [H 3 O + ] aq [74], it was shown that water molecules in the second hydration shell could help promote the proton transfer from H 3 O + to H 2 O, through the formation of the Zundel complex (H 5 O 2 + ).…”
Section: [Li + /Ala] Aqmentioning
confidence: 85%